Regional differences in injury incidence in European professional football - Walden, M.; Hägglund, M.; Orchard, J.; Kristenson, K.; Ekstrand, J. (Scandinavian Journal of Medicine & Science in Sports, 2013)
The objective of this study was to investigate regional differences in injury incidence in men's professional football in Europe. A nine-season prospective cohort study was carried out between 2001-2002 and 2009-2010 involving 1357 players in 25 teams from nine countries. Teams were categorized into different regions according to the Köppen-Geiger climate classification system. Teams from the northern parts of Europe (n = 20) had higher incidences of injury overall [rate ratio 1.12, 95% confidence interval (CI) 1.06 to 1.20], training injury (rate ratio 1.16, 95% CI 1.05 to 1.27), and severe injury (rate ratio 1.29, 95% CI 1.10 to 1.52), all statistically significant, compared to teams from more southern parts (n = 5). In contrast, the anterior cruciate ligament injury incidence was lower in the northern European teams with a statistically significant difference (rate ratio 0.43, 95% CI 0.25 to 0.77), especially for noncontact anterior cruciate ligament injury (rate ratio 0.19, 95% CI 0.09 to 0.39). In conclusion, this study suggests that there are regional differences in injury incidence of European professional football. However, further studies are needed to identify the underlying causes.